Civil servants' activity regulation in Lithuania 1918-1940 - Palidauskaitė, Jolanta; Petrokaitė, Milda (Lietuvos istorijos studijos, 2010)
The focus of the article is the legal regulation of civil servants' activity in Lithuania during the period 1918-1940. In the introduction, authors emphasize that this topic received more attention from lawyers. The review of Constitutional statements (1918, 1919, 1920, 1922, 1928, 1938) in regards to civil servants, other laws, and legislation is presented. A short description of the historical situation when the new independent Lithuanian Republic had to create new state institutions, including civil service, based on the model of western democracies and overcome difficulties of Russian empire legacy helps understanding the peculiarities of the situation. For some time, the new Lithuanian and old Russian legislation regulating the activity of civil servants coexisted, and a special State Council had to decide which to take precedence.Civil service in Interwar Lithuanian Republic was built on the broad notion. Not only people with administering functions (real bureaucrats) but teachers, opera's singers, drivers, and others were considered as civil servants. Each of them had their place in the hierarchy. Legislation enacted during that period allows concluding that building civil service was not among the State's priorities. Different laws and rules regulated the activity of civil servants, describing their duties, salaries, social guarantees, and rights. Some aspects of their activity, such as enrolment, admission, career possibilities, and question of responsibility, were skipped in legislation. Despite some shortcomings of legal regulation, the status of civil servant in Lithuanian society was rather highly valued. In addition to salary, they had some social benefits for their families, and later were able to study in special courses. The relationship between qualification and salary was confirmed.The Constitution confirmed in 1938 mentioned that various aspects of civil servants' activity are regulated by Civil Service law. The draft of this law, together with some other legislation (how to prevent illegal enrichment of civil servants), was discussed, but drastic events of 1940 pulled back the realization of these ideas. Not only practitioners but scholars and lawyers participated in public discussions from 1935-1939, trying to find out how to make the work of bureaucrats more efficient, how to better control and organize their work, prevent the creation of new institutions and offices, etc. Public discussion and ideas of scholars were rather modern, progressive, and reminded ideas of famous authorities of management.The authors conclude the article raising the hypothetical question of what would happen if Lithuania adopted a new Civil Service Act as in Belgium and would not be occupied in 1940.
Keywords: -